Condrossarcoma mixoide em joelho de cão com ruptura do ligamento cruzado cranial - Relato de caso - Filgueira, Fabrícia Geovânia Fernandes [UNESP]; Minto, Bruno Watanabe [UNESP]; De Paula Coelho, Lívia [UNESP]; Souza, Érica Siqueira; Sembenelli, Guilherme [UNESP]; Wittmaack, Mônica Carolina Nery [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Dias, Luis Gustavo Gosuen Gonçalves [UNESP]; Moraes, Paola Castro [UNESP] (My University, 2016)
Our purpose is to relate a case of myxoid chondrosarcoma in a dog. A nine years old, female, Chow-Chow presenting left hind limb lameness was attended. At first, the patient was referred for surgical treatment of rupture of the left cranial cruciate ligament. During arthrotomy it was observed an irregular and rough periarticular surface without noticeable increase in bone volume in the distal femur. We opted for the collection of samples for histological analysis, which revealed a myxoid chondrosarcoma. Fifteen days after the amputation of the left hind limb was performed. Seven months following surgery, the animal had difficulty breathing and decreased appetite. Thoracic radiography was performed, identifying signs of lung metastasis. An esophageal tube was introduced to enteral feeding of patients. Days after the animal showed worsening of symptoms and the owner chose not to do chemotherapy but euthanasia. Although surgery allowed the animal a good survival rate was not sufficient to prevent development of metastases, which makes to consider adjuvant therapies such as chemotherapy may be required. Additionally, we show the importance of observing the macroscopic appearance of tissues during bone and joint surgery.
Myxoid chondrosarcoma in dog knee with rupture of the cranial cruciate ligament - Case report
Keywords: Canine; Cartilage; Joint; Neoplasy